Nigeria land governance reform: What needs to be done to stimulate demand and support market growth? - Ghebru, Hosaena; Kennedy, Adam (Michigan State University, 2019)
Over the last decade, land tenure reform and enhanced tenure security have been given greater attention by African governments, including Nigeria, as policy tools to encourage agricultural growth and to alleviate poverty. Land tenure security can generate agricultural investment incentives and lead to increased agricultural productivity through three channels (Besely 1995). First, it promotes long term investment in land by reducing expropriation risk. Second, it encourages investment by lowering transaction costs and allowing more productive farmers to purchase or rent land from less productive farmers, making both parties better off. Third, it reduces asymmetric information about land ownership rights, allowing individuals to use their land as collateral for loans encouraging investment. Less than 3 percent of the land in Nigeria is formally registered leaving the vast majority of the population to deal with tenure insecurity and its attendant negative implications on land related investment and agricultural productivity. This brief will examine current land policy and administration in Nigeria, landholders demand for tenure security, and present recommendations to improve administration of land.